THE STRATEGY OF ODED-YANA IN WINNING YOUTH VOTES AT BANDUNG REGION ELECTION 2018 - Azmi, Mohammad Fazrulzaman (Civic Education Department, Faculty of Teacher Training and Education, University of Muham, 2020)
Abstrak This research describes Oded-Yana's strategy in winning youth votes at Bandung Regional Election 2018. This study uses a qualitative approach, with data collection techniques through interviews and documentation studies. The results of this study indicate that, Oded-Yana won the youth vote by attracting their attention through the Youth Space and Co Working Space program, using hijra narratives and utilizing political incentives from Ridwan Kamil and Asyik (Ajat-Syaikhu), and conducting social media-based campaigns and Internet. After that, Oded-Yana visited a youth gathering place and used the peer to peer method. In the process Oded-Yana divides youth segments, then visits them or implements a door to door campaign strategy, and builds mutual understanding. Furthermore, Oded-Yana is connected with youth by optimizing the functions of the media center and secretariat, as well as improving connections with youth through network optimization. Later, Oded-Yana formed volunteers, and gave them responsibility and made them campaign leaders, as was the Boy Band Volunteer (Balad Oded-Yana for Bandung) with the Ruko and Nobar program. In addition, Oded-Yana uses music and culture to empower the community, as does the KPJ (Komunitas Penyanyi Jalanan). Thus, Oded-Yana did various ways to win the youth votes, but the main approach used was to meet the nodes of youth leaders, and build political contracts with him, so that they would commit to supporting candidates.